(untitled) (Annals of Medical Research, 2025)
Aim: In this study, we aimed to examine the sociodemographic and clinical characteristics of geriatric patients receiving inpatient treatment in the psychiatry clinic of a university hospital. Materials and Methods: This retrospective study was conducted by examining the medical records of patients aged 65 and over who received psychiatric treatment between January 1, 2018 and December 31, 2023. Data related to the patients were obtained from the electronic patient database of the hospital. Results: A total of 252 patients, consisting of 124 females and 128 males, were included in the study. The mean age of the patients was 70.67 ± 5.01 years, and the average length of hospital stay was 17.35 ± 12.18 days. The diagnoses were, respectively, anxiety disorder (46.8%), depression (25.0%), mood disorder (10.7%), psychotic disorders (8.3%), alcohol/substance dependence (2.0%), psychiatric disorders related to general medical conditions (4.8%), dementia (1.2%), and intellectual disability (0.4%). In total, 22.8% had received inpatient treatment more than once. The condition that most often caused repeated hospitalizations was anxiety disorder, and 39% of these patients had a coexisting chronic disease. Depression was the most common mental disorder accompanying anxiety (15.3%). Mild or higher dementia was detected in 24 of 64 patients who underwent Mini-Mental State Examination. While the rates of comorbid chronic diseases were high in patients with Yeşil Kart (s form of preliminary social security), the rate of female patients hospitalized due to psychotic disorders was higher than that of males Conclusion: Determining the frequency of psychiatric disorders in hospitalized elderly patients and knowing the characteristics that case repeated hospitalization will contribute to the planning and development of appropriate treatment strategies.